Revolution from above in English schools: neoliberalism, the democratic commons and education - Stevenson, Nick (SAGE, 2015)
The ideas of the New Left and the recently emerged alter-globalisation movements are marginal within current policy debates concerning the English education system. Here I seek to demonstrate the interconnections between the New Left and the alter-globalisation movement and suggest that these ideas contain a powerful corrective to the increasingly authoritarian present. The next part of the article considers the development of neoliberalism both in a theoretical context and since the arrival of the new Conservative–Liberal government in the UK. Here I outline the rapid transformation of English schools under the academies programme and look at how it has been explicitly linked to ideas of ‘moral collapse’ evident in the popular discourse of ‘Broken Britain’. Especially significant in this respect has been the labelling of comprehensive schools as ‘failures’ and the explicit imposition of more authoritarian understandings of pedagogy. I seek to explore both the rapidity of this transformation in the context of the dissatisfaction with the idea of comprehensive schools shown by the political Right and the Third Way’s reworking of socialism. Finally I briefly consider more progressive alternatives for schools and education by returning to the idea of the democratic commons. In this respect, the cultural Left needs to explore more radical alternatives beyond the defence of comprehensive schooling which sounds both nostalgic and misplaced within our global times.